1998
DOI: 10.1063/1.122289
|View full text |Cite
|
Sign up to set email alerts
|

Field emission properties of GaN films on Si(111)

Abstract: GaN thin films were grown by electron cyclotron resonance molecular beam epitaxy on Si(111) wafers. X-ray diffraction and transmission electron microscopy revealed that the thin films were single crystals with a hexagonal symmetry and a clear textured structure. The average column size was determined to be close to 100 nm in diameter. Despite the large defect density, a strong room temperature photoluminescence signal with a full width at half maximum of 138 meV was observed from these samples. The surface exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 9 publications
1
15
1
Order By: Relevance
“…L 909 ever, the present turn-on electric field is the lowest value compared with those reported previously 4,14,[18][19][20][21] except for that in ref. 22.…”
Section: Surfacecontrasting
confidence: 69%
“…L 909 ever, the present turn-on electric field is the lowest value compared with those reported previously 4,14,[18][19][20][21] except for that in ref. 22.…”
Section: Surfacecontrasting
confidence: 69%
“…5(a), it can be found that the turn-on field of the InGaN nanowires is 10 V/mm. The turn-on field is much lower than that of GaN thin films [25] and comparable to that of GaN nanowires [20], but much higher than that of GaAs nanowires [26], GaN nanorod [27] and CNTs [28]. The emission current density reaches about 2.9 mA/cm 2 at an applied field of about 24 V/ mm.…”
Section: Resultsmentioning
confidence: 90%
“…The previously reported turn-on electric field has ranged approximately between 7 and 133 V/μm for the GaN pyramid arrays and the roughened GaN surface [2][3][4][5], and between 1.25 and 40 V/μm for the GaN nanorod or nanocolumn films [6,7] although it is rather difficult to compare all of them under the same measurement conditions. On the other hand, the values of 1.5 × 10 2 [5] and 4.96 × 10 3 [7] have been reported as β'.…”
Section: Resultsmentioning
confidence: 96%
“…To this effect, the studies on the application of GaN for field emitters have been carried out concentrating on the formation of sharp tips [1][2][3][4][5][6][7]. The approaches developed so far are fabrication of array of pyramid-shape GaN by selective area growth [1][2][3][4], roughening the surface of GaN epilayer by plasma etching [5], spontaneous tip formation during columnar growth [6], and so on. Recently, the dramatic reduction in turn-on electric field has been achieved for the nanorod film grown on Si substrates with native oxides [7].…”
mentioning
confidence: 99%